Clinical presentation and treatment outcomes of extrapulmonary nontuberculous mycobacterial infections with rapid and slow growth rates in Cali, Colombia - Juanita María Parra-Villamil; Natalia Ramos-Ospina; Sofia Alexandra Montes-Tello; Angie Valeria Torres-Morales; Mabel Moreno-Turriago; José Fernando García-Goez (BMC Infectious Diseases)
Abstract Introduction The increasing prevalence of extrapulmonary nontuberculous mycobacterial (NTM) infections poses significant challenges in clinical management due to their inherent drug resistance, the need for prolonged antibiotic regimens and the complexities associated with surgical management. Although these infections are infrequent in daily clinical practice, detailed information on associated clinical outcomes is lacking in the local literature. Materials and methods This descriptive observational study examined 17 patients with extrapulmonary NTM infection from the General Mycobacteria Registry of Fundación Valle del Lili University Hospital (FVL), a leading reference care center located in Cali, a city in southwestern Colombia. Notably, Cali is classified as a high-risk area for tuberculosis. The study reviewed a total of 391 patients between 2007 and 2021. Results A predominance of women with a history of cosmetic surgery was observed, with the skin being the most common site of involvement, especially for M. fortuitum complex and M. abscessus complex. Clarithromycin based therapy was given to 14/18 (82.3%) of the patients. The mean duration of treatment was 4–6 months, for a cure rate of 15/17 (88.2%). Conclusion The treatment regimens implemented mostly align with the literature recommendations. However, it is essential to note that while the observed cure rate exceeds 80%, this assertion is tempered by the limitation imposed by the lack of confirmatory imaging in some cases. A contributing factor to the higher cure rate observed in this study may be the use of more extensive surgical interventions, with some patients undergoing more than one procedure. Given the limited number of case series on extrapulmonary nontuberculous mycobacterial infections, these findings emphasize the potential importance of surgical management in achieving higher cure rates. The observed cure rate suggests potentially better clinical management of these infections in our region and underscores the need for future research to understand the factors contributing to this comparative therapeutic success.